Ceramic tile glue
By using artificial sand prepared from lithium slag and general-purpose silicate cement, and optimizing the particle size distribution of the tile adhesive, the problems of easy hollowing and falling off of tile adhesive were solved, achieving efficient and economical bonding effect, suitable for the construction of high-quality tiles.
Patent Information
- Application Number
- CN202511119056.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-11
- Publication Date
- 2025-10-17
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing tile adhesives are prone to hollowing and falling off during construction, especially when pasting on substrates with large deformations. In addition, traditional solutions are costly, which limits their widespread application.
Artificial sand prepared from lithium slag is used as the main raw material, combined with general-purpose silicate cement and cellulose ether to form a dense structure with coarse aggregate support and fine cement particles filling. The particle size distribution is optimized and antibacterial agents are added to improve the bonding strength and durability.
It achieves efficient tile bonding, reduces production costs, improves construction efficiency, is highly adaptable, and is suitable for bonding high-quality tiles, especially exhibiting excellent bonding performance on substrates such as gypsum board and wood.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of adhesives, in particular to a tile adhesive. Background Art
[0002] With its beautiful, durable and easy-to-clean features, ceramic tiles have become one of the most widely used finishing materials in the field of architectural decoration, and occupy an important position in various decorative scenes such as walls and floors.
[0003] However, during the tile installation process, hollowing of tiles often occurs due to various factors, including the construction process and material compatibility. This problem not only affects the smoothness and aesthetics of the decorative surface, but can also cause the tiles to loosen and fall off. In severe cases, it can even endanger their safety, significantly reducing the quality and service life of the decorative project. Therefore, it has become a key technical challenge that needs to be urgently addressed in the industry.
[0004] To improve tile bonding quality and reduce hollowing, the industry has adopted polymer-modified cement mortar. Practice has shown that polymer-modified cement mortar is highly effective in bonding certain tile materials. Under standardized construction procedures, it can effectively reduce hollowing and significantly improve bonding strength.
[0005] However, for attaching high-quality ceramic tiles, especially on highly deformable substrates like gypsum board and wood, traditional solutions often rely on adding large amounts of redispersible rubber powder to the tile adhesive. While significantly increasing the amount of rubber powder can improve the adhesive's flexibility to accommodate substrate deformation and achieve performance indicators that meet the C2 requirements of the JC / T547-2017 "Ceramic Tile Adhesive" standard, this approach significantly increases adhesive costs, making it uneconomical for large-scale engineering applications and limiting its wider adoption. Summary of the Invention
[0006] In order to solve the above technical problems, the present invention provides a new type of tile adhesive, which overcomes the problems of easy hollowing and falling off of tile adhesive in the prior art and poor adaptability of construction process.
[0007] In one aspect, the present invention provides a tile adhesive comprising the following raw materials in percentage by mass:
[0008] Artificial sand 60~70%,
[0009] Cement 28.5~39.3%,
[0010] Cellulose ether 0.2~0.5%,
[0011] Additives 0.5~1%.
[0012] Further, the artificial sand comprises ingredients in percentage by mass: 80-85% of lithium residue, 5-10% of mineral powder, 5% of cement, 3-5% of fly ash, and 1-2% of plasticizer.
[0013] Further, the cement is general portland cement, and the cement strength grade is at least one of 42.5, 42.5R, 52.5, and 52.5R.
[0014] Further, the plasticizer is at least one of corn starch, waxy rice starch, bentonite, Guangzhou white clay, and Guangzhou black clay.
[0015] Further, the additive comprises at least one of an antibacterial agent, a water-retaining agent, and a reinforcing agent.
[0016] Further, the reinforcing agent is dispersible latex powder or calcium formate.
[0017] Further, the average particle size of the artificial sand is 0.1-0.5 mm.
[0018] Further, the lithium residue has a bulk density of 1.0-1.2 g / cm 3 , and a specific surface area of 400-600 m 2 / kg.
[0019] Further, the mineral powder is granulated blast furnace slag S95 mineral powder or above, and has a specific surface area of 450-600 m 2 / kg.
[0020] Further, the antibacterial agent is at least one of chitosan, quaternary ammonium salt, and silver-based antibacterial agent. The addition of the antibacterial agent in the ceramic tile adhesive can effectively inhibit the growth of bacteria, so that the ceramic tile adhesive can be applied to places with high sanitary requirements.
[0021] Further, the cellulose ether is at least one of hydroxypropyl methylcellulose and methylcellulose. The hydroxyl groups in the cellulose ether form hydrogen bonds with water molecules, thereby achieving thickening and water retention effects, improving the viscosity of the ceramic tile adhesive, enhancing the anti-sagging ability, and ensuring the flatness of the vertical paving of the ceramic tiles.
[0022] Further, the artificial sand is prepared by the following method:
[0023] Drying the lithium residue;
[0024] Proportioning and batching the ingredients of the artificial sand;
[0025] Grinding to 300-500 mesh;
[0026] Adding 12-15% of water by mass of the batch, and stirring uniformly;
[0027] Granulating and shaping;
[0028] Pre-curing 12~20h;
[0029] Curing 7~28d;
[0030] Drying, screening, and artificial sand is prepared.
[0031] Further, the artificial sand is prepared by the following method:
[0032] Lithium slag is water-sprayed and ground to 200~400 mesh;
[0033] Dehydration;
[0034] According to the component proportioning of the artificial sand, ingredients are prepared;
[0035] High-speed precision mixing;
[0036] Granulation and shaping;
[0037] Pre-curing 12~20h;
[0038] Curing 7~28d;
[0039] Drying, screening, and artificial sand is prepared.
[0040] The artificial sand prepared by the above method has lithium slag as the main component, not only reasonably utilizes the industrial solid waste of lithium slag, but also is lighter than ordinary sand, and has a bulk density of 1200~1300kg / m 3 As the main component of the ceramic tile glue, the coating rate of the ceramic tile glue during use can be improved; and the artificial sand has water absorption and water retention functions, so that the use amount of thickening agents such as cellulose ether can be reduced, thereby reducing the cost of the ceramic tile glue.
[0041] Further, the lithium slag is derived from lepidolite or spodumene.
[0042] Compared with the prior art, the present application has the following beneficial effects:
[0043] The ceramic tile glue provided by the present application takes artificial sand prepared from lithium slag as the core raw material, realizes high-proportion resource utilization of lithium slag industrial solid waste, effectively alleviates the pressure of solid waste disposal; the added artificial sand has high strength, strong water absorption and water retention, is small in conventional bulk density, is light in quality, significantly improves the coating rate of the ceramic tile glue, and greatly improves the construction efficiency; and ordinary cement is added, which forms a dense structure of coarse aggregate support + fine cement particle filling with the artificial sand, and through optimization of the particle gradation, the strength, durability and economy are significantly improved. Since the use of the artificial sand can reduce the use amount of thickening agents such as cellulose ether, the production cost of the ceramic tile glue is reduced. The ceramic tile glue prepared by the present application has a performance of C2 level, excellent bonding strength and technical reliability, and is suitable for popularization and use. DETAILED DESCRIPTION
[0044] The technical solutions in the embodiments of the present application will be clearly and completely described below with reference to the embodiments of the present application. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments of the present application. Based on the embodiments of the present application, all other embodiments obtained by a person of ordinary skill in the art without creative effort belong to the protection scope of the present application.
[0045] A ceramic tile glue comprises the following raw materials in percentage by mass:
[0046] Artificial sand 60~67.5%,
[0047] Cement 28.5~39.3%,
[0048] Cellulose ether 0.2~0.5%,
[0049] Additive 0.5~1%.
[0050] In specific embodiments, the artificial sand comprises the following components in percentage by mass: lithium slag 80~85%, mineral powder 5~10%, cement 5%, fly ash 3~5%, and plasticizer 1~2%.
[0051] In specific embodiments, the cement is general Portland cement, and the cement strength grade is at least one of 42.5, 42.5R, 52.5, and 52.5R.
[0052] In specific embodiments, the plasticizer is at least one of corn starch, waxy rice starch, bentonite, Guangzhou white clay, and Guangzhou black clay.
[0053] In specific embodiments, the additive comprises at least one of an antibacterial agent, a water-retaining agent, and a reinforcing agent.
[0054] In specific embodiments, the reinforcing agent is dispersible latex powder or calcium formate.
[0055] In specific embodiments, the average particle size of the artificial sand is 0.1~0.5mm.
[0056] In specific embodiments, the lithium slag has a bulk density of 1.0~1.2g / cm 3 , and a specific surface area of 400~600m 2 / kg.
[0057] In specific embodiments, the mineral powder is granulated blast furnace slag S95 mineral powder and above grade, and has a specific surface area of 450~600m 2 / kg.
[0058] In specific embodiments, the antibacterial agent is at least one of chitosan, quaternary ammonium salt, and silver-based antibacterial agent.
[0059] In a specific embodiment, the cellulose ether is at least one of hydroxypropyl methylcellulose, methylcellulose.
[0060] In one embodiment, the artificial sand is prepared by a first method:
[0061] The lithium residue is dried;
[0062] The ingredients are proportioned by mass percentage as follows: 80-85% of lithium residue, 5-10% of mineral powder, 5% of cement, 3-5% of fly ash, and 1-2% of plasticizer, and are stirred uniformly;
[0063] The proportioned ingredients are ground to 300-500 mesh by a Raymond mill, a superfine ring roller mill, or a vertical mill;
[0064] Water accounting for 12-15% of the mass percentage of the ground ingredients is added and stirred uniformly to form wet material;
[0065] The wet material is granulated by a disc granulator or an extrusion granulator, and the granulated material is shaped by an impact sand making machine or a VSI sand making machine to form artificial sand particles with an average particle size of 0.1-0.5 mm;
[0066] Pre-curing: The artificial sand after granulation and shaping is evenly laid in a curing tray with a thickness controlled at 10-15 cm, the curing tray is placed in a pre-curing chamber, the curing temperature is set at 20-25°C, the sand body humidity is 65-75%, and the pre-curing time is 12-20 h; the substances in the raw materials are caused to slowly undergo hydration reaction, and a preliminary structural network is formed inside the sand body;
[0067] Curing: the temperature is maintained at 20-22°C, the sand body humidity is maintained at 80-85%, and the curing time is 15-28 d to fully densify the internal structure of the artificial sand;
[0068] Drying and screening: first drying at 150-180°C for 1-2 h, then drying at 120-150°C for 0.5-1 h, and finally screening the dried artificial sand by a vibrating screen to obtain artificial sand with the required particle size.
[0069] In one embodiment, the artificial sand is prepared by a second method:
[0070] The lithium residue is ground to 200-400 mesh by a ball mill or a sand mill after multiple water spraying;
[0071] Dehydration by pressure filtration, and the filtrate is recycled for the water spraying step of the lithium residue; after 5-10 cycles, the filtrate can be used for extracting lithium ions;
[0072] The ingredients are proportioned by mass percentage as follows: 80-85% of the lithium residue after pressure filtration, 5-10% of mineral powder, 5% of cement, 3-5% of fly ash, and 1-2% of plasticizer, and are stirred;
[0073] Fine mixing is performed with a high-speed mixer;
[0074] The wet material is granulated by using a disc granulator or an extrusion granulator, and the granulated material is shaped by using an impact sand making machine or a VSI sand making machine to form artificial sand particles with an average particle size of 0.1-0.5 mm;
[0075] Pre-curing: the artificial sand after granulation and shaping is evenly laid in a curing tray, the thickness is controlled to be 10-15 cm, the curing tray is placed in a pre-curing chamber, the curing temperature is set to be 20-25℃, the sand body humidity is 65-75%, and the pre-curing time is 12-20 h; the substances in the raw materials are caused to slowly undergo hydration reaction, and a preliminary structure network is formed in the sand body;
[0076] Curing: the temperature is maintained at 20-22℃, the sand body humidity is maintained at 80-85%, and the curing is performed for 15-28 d to fully densify the internal structure of the artificial sand;
[0077] Drying and screening: first drying at 150-180℃ for 1-2 h, then drying at 120-150℃ for 0.5-1 h; finally, the artificial sand after drying is screened by using a vibrating screen to obtain artificial sand with a required particle size.
[0078] Example 1
[0079] Each raw material is prepared according to the following formula, and then mixed uniformly to obtain the ceramic tile glue;
[0080] The specific mass ratio of each raw material of the ceramic tile glue of the example is as follows:
[0081] Artificial sand 70%,
[0082] 42.5 cement 28.5%,
[0083] Hydroxypropyl cellulose 0.5%
[0084] Dispersible latex powder 0.1%
[0085] Calcium formate 0.5%
[0086] Chitosan 0.4%;
[0087] The artificial sand is prepared by using the first method, and specifically:
[0088] The lithium slag is dried;
[0089] The ingredients are proportioned according to the mass percentage of 80% lithium slag, 10% mineral powder, 5% cement, 4% fly ash and 1% corn starch, and are uniformly stirred;
[0090] The above ingredients are ground to 400 mesh by using a Raymond mill;
[0091] Add 13% water by weight to the ground ingredients and stir evenly to form a wet material;
[0092] The disc granulator is used for granulation, and the impact sand making machine is used to shape the granulated material to form artificial sand with an average particle size of 0.5 mm;
[0093] Pre-curing: Spread the granulated and shaped artificial sand evenly on the curing tray with a thickness of 15 cm. Place the curing tray in the pre-curing room and set the curing temperature at 20°C, the sand body humidity at 65%, and the pre-curing time at 20 hours. This will promote the slow hydration reaction of the raw materials and form a preliminary structural network inside the sand body.
[0094] Curing: The temperature is maintained at 20℃ and the humidity of the sand is maintained at 83%. Curing is carried out for 15 days to fully densify the internal structure of the artificial sand.
[0095] Drying and screening: First dry at 150℃ for 2 hours, then dry at 130℃ for 0.5 hours; finally, use a vibrating screen to screen the dried artificial sand to obtain artificial sand of the required particle size.
[0096] Example 2
[0097] Prepare the raw materials according to the following formula and mix them evenly to obtain tile adhesive;
[0098] The specific mass ratios of the raw materials of the tile adhesive in this embodiment are as follows:
[0099] Artificial sand 60%,
[0100] 52.5 cement 39.3%,
[0101] Methylcellulose 0.2%,
[0102] Quaternary ammonium salt 0.5%;
[0103] Among them, artificial sand is prepared by the second method, specifically:
[0104] Spray the lithium slag with water several times and grind it to 300 mesh using a ball mill or sand mill;
[0105] Press filter dehydration, the filtrate is recycled for the lithium slag water spraying step, and after 10 cycles, the filtrate is used to extract lithium ions;
[0106] Prepare materials according to the mass percentage of 85% lithium slag, 5% mineral powder, 5% cement, 4% fly ash and 1% bentonite, and stir;
[0107] Use a high-speed mixer for fine mixing;
[0108] The wet material is granulated by using an extrusion granulator, and the granulated material is shaped by using a VSI sand making machine to form artificial sand particles with an average particle size of 0.3 mm;
[0109] Pre-curing: The artificial sand after granulation and shaping is evenly laid in a curing tray with a thickness of 12 cm, the curing tray is placed in a pre-curing chamber, the curing temperature is set to 22℃, the sand body humidity is 70%, and the pre-curing time is 20h; to promote the slow hydration reaction of the materials in the raw materials, and form a preliminary structure network inside the sand body;
[0110] Curing: The temperature is maintained at 22℃, the sand body humidity is maintained at 85%, and the curing is carried out for 28d to fully densify the internal structure of the artificial sand;
[0111] Drying and screening: first drying at 180℃ for 1.5h, then drying at 130℃ for 1h; finally, the artificial sand after drying is screened by using a vibrating screen to obtain artificial sand with the required particle size.
[0112] Example 3
[0113] Prepare each raw material according to the following formula, and then mix uniformly to obtain a ceramic tile glue;
[0114] The specific mass ratio of each raw material of the ceramic tile glue of this example is as follows:
[0115] Artificial sand 65%,
[0116] 42.5R cement 34%,
[0117] Hydroxypropyl cellulose 0.2%,
[0118] Chitosan 0.8%;
[0119] Among them, the artificial sand is prepared by the first method, specifically:
[0120] The lithium slag is dried;
[0121] The ingredients are mixed according to the mass percentage ratio of lithium slag 85%, mineral powder 5%, cement 5%, fly ash 3% and 2% bentonite, and stirred uniformly;
[0122] The above ingredients are ground to 300 mesh by using a Raymond mill;
[0123] Add water accounting for 15% of the mass percentage of the ground ingredients, and stir uniformly to form a wet material;
[0124] Granulation is carried out by using a disc granulator, and the granulated material is shaped by using an impact type sand making machine to form artificial sand particles with an average particle size of 0.1 mm;
[0125] Pre-curing: After the granulation and shaping of the artificial sand, the artificial sand is evenly laid in the curing tray with a thickness of 10 cm, the curing tray is placed in the pre-curing chamber, the curing temperature is set to 25 DEG C, the humidity of the sand body is 80%, and the pre-curing time is 20 h; the substances in the raw materials are caused to slowly undergo hydration reaction, and a preliminary structure network is formed in the sand body;
[0126] Curing: the temperature is maintained at 22 DEG C, the humidity of the sand body is maintained at 80%, and the curing is performed for 20 d, so that the internal structure of the artificial sand is fully densified;
[0127] Drying and screening: first drying at 180 DEG C for 1 h, then drying at 150 DEG C for 0.5 h; finally, the artificial sand after drying is screened using a vibrating screen to obtain artificial sand with the required particle size.
[0128] Comparative Example 1
[0129] Each raw material is prepared according to the following formula, and then mixed and stirred uniformly to obtain the ceramic tile glue;
[0130] The specific mass ratio of each raw material of the ceramic tile glue of the present comparative example is as follows:
[0131] 42.5 cement 0.28 kg,
[0132] Quartz sand 0.65 kg,
[0133] Fly ash 70 kg,
[0134] Hydroxypropyl methylcellulose ether 0.0018 kg.
[0135] The ceramic tile glue of Examples 1-3 and Comparative Example 1 is detected, and the detection method is the ceramic tile glue detection method specified in JC / T 547-2017 "Ceramic Wall and Floor Tile Adhesive". The results are shown in Table 1.
[0136] Table 1
[0137] Item Tensile adhesive strength (Mpa) Tensile adhesive strength after water immersion (Mpa) Tensile adhesive strength after heat aging (Mpa) Tensile adhesive strength after freeze-thaw cycle (Mpa) Tensile adhesive strength after standing for 20 min (Mpa) Example 1 2.2 1.8 2.4 1.8 1.6 Example 2 2.5 2.1 2.4 1.9 1.7 Example 3 2.0 1.6 1.9 1.7 1.2 Comparative Example 1 1.5 1.2 1.4 1.2 1.0
[0138] As can be seen from Table 1, the ceramic tile glue of the present application has significant advantages in various performance tests, has excellent initial bonding strength, water resistance, high temperature resistance and freeze-thaw resistance, meets the requirements of ceramic tile glue C2 level, and has strong construction practicability, and is suitable for popularization and use.
[0139] The above describes the present application with specific examples, but it should be understood that the specific description should not be understood as limiting the essence and scope of the present application, and various modifications of the above examples made by those skilled in the art after reading the present specification are within the scope of the present application.
Claims
1. A tile adhesive, characterized in that: The raw materials include the following percentages by mass: Artificial sand 60~70%, Cement 28.5~39.3%, Cellulose ether 0.2~0.5%, Additives 0.5~1%.
2. The tile adhesive according to claim 1, characterized in that The artificial sand comprises the following components by mass percentage: 80-85% of lithium slag, 5-10% of mineral powder, 5% of cement, 3-5% of fly ash and 1-2% of plasticizer.
3. The tile adhesive according to claim 2, characterized in that The plasticizer is at least one of corn starch, glutinous rice starch, bentonite, Guangzhou white mud and Guangzhou black mud.
4. The tile adhesive according to claim 1, characterized in that The additive is at least one of an antibacterial agent, a water-retaining agent, and an enhancer.
5. The tile adhesive according to claim 1, characterized in that The average particle size of the artificial sand is 0.1-0.5 mm.
6. The tile adhesive according to claim 2, characterized in that: The bulk density of the lithium slag is 1.0-1.2 g / cm 3 , with a specific surface area of 400~600m 2 / kg.
7. The tile adhesive according to claim 2, characterized in that: The ore powder is granulated blast furnace ore powder S95 or above, with a specific surface area of 450~600m 2 / kg.
8. The tile adhesive according to claim 2, characterized in that: The artificial sand is prepared by the following method: Lithium slag drying; Mix ingredients according to the proportion of artificial sand; Grind to 300~500 mesh; Add 12-15% water by weight of the ingredients and stir evenly; Granulation and shaping; Pre-curing 12~20h; Curing 7~28d; Drying and screening to produce artificial sand.
9. The tile adhesive according to claim 2, characterized in that: The artificial sand is prepared by the following method: Lithium slag is water-jet ground to 200-400 mesh; Dehydration Mix ingredients according to the proportion of artificial sand; High-speed fine mixing; Granulation and shaping; Pre-curing 12~20h; Curing 7~28d; Drying and screening to produce artificial sand.
10. The tile adhesive according to claim 2, characterized in that: The lithium slag is derived from lepidolite or spodumene.